Solar PV modelling at local level - Raw Data - Balta-Ozkan, Nazmiye; Hart, Phil; Truckell, Ian; Yildirim, Julide; Connor, Peter (Cranfield University, 2021)
This dataset includes the raw data used in the modelling of solar PV adoption at LAD level. For description of the variables, please refer to Table 4 of the journal article titled 'Energy transition at local level: analyzing the role of peer effects and socio-economic factors on UK solar photovoltaic deployment'.
Keywords: 'local energy data'; 'UK solar PV data'; 'UK socio-economic data'; 'Econometric and Statistical Methods'